APLIKASI MINYAK SEREH WANGI (Citronella Oil) DAN GERANIOL DALAM PEMBUATAN SKIN LOTION PENOLAK NYAMUK - Dwi Setyaningsih, Erliza Hambali dan Muharamia Nasution (Jurnal Teknologi Industri Pertanian, 2007)
ABSTRACTIndonesia is one of the biggest producers of citronella oil in the world. The high production of citronella oil needs to be developed becoming new fractions and application into product. One of the applications is as active component in insect repellant in skin lotion product. In this research, skin lotion was produced by addition of citronella oil and geraniol as active component with parameter of percentage of active component (5.0, 7.5, and 10.0%) and three alternatives of process (process 1, process 2, and process 3). The parameters of analyses were emulsion stability, viscosity, emulsion capacity, pH, and total microbe.Citronella oil used in this research has several characteristics; namely density 0.8352, index refraction 1.4558, citronellal content 5.8% and geraniol content 2.4%. The result of this analysis show that addition of geraniol 5.0% in process 2 produced  the highest viscosity was 1.55 (x300 cP), the lowest pH (3.47), the highest emulsion stability (62.29%) and the lowest emulsion capacity (2.15). The conclusion according to that result was process 2 was produced the best of skin lotion formulation. In the next research all of the action from process 2 used for effectiveness experiment to mosquito bite. The results of the experiment show that all of skin lotions gave negative result to amount of mosquito bite at rabbit. Decreasing fraction of active component until 0.1% showed positive result by one bite of mosquito in the rabbit skin.